Towards an immunization perfect model? - de la Peña, Joseba Iñaki; Iturricastillo, Iván; Moreno-Ruiz, Rafael; Román, Francisco; Trigo-Martínez, Eduardo (Wiley, 2020)
Immunization is an investment strategy often used by insurance companies. Usually, this strategy takes into account the first- and second-order of Taylor series (Duration and Convexity). However, the model itself has risk because of the difference between the real and estimated value via duration and convexity approximation. Therefore, the aim of this article is to find a better immuniza- tion model avoiding the effect of unexpected interest rate shocks by adding more terms of Taylor series to an immunization strategy. As criteria of efficiency, the paper checks the effect of interest rate risk in several immunization models upon a 99.5% confidence level (risk level of 1 in 200 scenarios), as required by Solvency II in Europe, to determine a better immunization strategy. This work analyses the skewness and, consequently, the fitness of adding third- and fourth-order Taylor series. The main finding is that the model with four factors avoids the influence of interest rate shocks. Therefore, the capital on risk in near zero.
https://openpolicyfinder.jisc.ac.uk/id/publication/7471
Keywords: Seguros; Gestión del riesgo; Asset-liability management; Immunization; Interest rate risk; Solvency capital requirement